2021
DOI: 10.3390/children8070543
|View full text |Cite
|
Sign up to set email alerts
|

Foundational Movement Skills and Play Behaviors during Recess among Preschool Children: A Compositional Analysis

Abstract: This study aimed to examine the associations between play behaviors during preschool recess and foundational movement skills (FMS) in typically developing preschool children. One hundred and thirty-three children (55% male; mean age 4.7 ± 0.5 years) from twelve preschools were video-assessed for six locomotor and six object-control FMS using the Champs Motor Skill Protocol. A modified System for Observing Children’s Activity and Relationships during Play assessed play behaviors during preschool recess. Associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 68 publications
(111 reference statements)
0
18
0
Order By: Relevance
“…In addition, studies needed to provide anthropometric and demographic data including age, sex, and area-level socioeconomic status. Where published, details of these studies can be found elsewhere [ 22 , 28 , 29 , 30 , 31 , 32 , 33 ]. Investigators with a major involvement in the eligible studies (e.g., past PhD students, co-supervisors) were approached by email and invited to contribute individual participant data to allow for data harmonisation and subsequent pooled analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, studies needed to provide anthropometric and demographic data including age, sex, and area-level socioeconomic status. Where published, details of these studies can be found elsewhere [ 22 , 28 , 29 , 30 , 31 , 32 , 33 ]. Investigators with a major involvement in the eligible studies (e.g., past PhD students, co-supervisors) were approached by email and invited to contribute individual participant data to allow for data harmonisation and subsequent pooled analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline data for this study were drawn from the 2010 Active Play Project, which has been reported in detail elsewhere [ 7 , 29 , 30 , 31 , 32 , 33 ]. In brief, the Active Play Project was a Local Authority funded programme in response to a growing awareness of a need to establish health behaviours, such as increased PA, and promote fitness from an early age [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Assessments such as The Functional Movement Screen [14] and the Foundational Movement Skills Tests [15] have been used to measure movement competencies required for pro cient participation in physical activity. No current assessment exists to determine how often limb movements are utilized during childhood activities such as recess.…”
Section: Gap In Current Assessment Toolsmentioning
confidence: 99%